2015
DOI: 10.2337/dc15-0781
|View full text |Cite|
|
Sign up to set email alerts
|

Alogliptin, a Dipeptidyl Peptidase 4 Inhibitor, Prevents the Progression of Carotid Atherosclerosis in Patients With Type 2 Diabetes: The Study of Preventive Effects of Alogliptin on Diabetic Atherosclerosis (SPEAD-A)

Abstract: OBJECTIVERecent experimental studies have shown that dipeptidyl peptidase 4 (DPP-4) inhibitors have antiatherosclerotic benefits in glucagon-like peptide 1-dependent and -independent manners. The current study investigated the effects of alogliptin, a DPP-4 inhibitor, on the progression of carotid atherosclerosis in patients with type 2 diabetes mellitus (T2DM). RESEARCH DESIGN AND METHODSThis prospective, randomized, open-label, blinded-end point, multicenter, parallelgroup, comparative study included 341 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
109
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 40 publications
1
109
1
6
Order By: Relevance
“…Так, име-ются данные, что гипер-и дислипидемия часто ассоци-ируются с ростом уровня СРБ, т.е. имеет место содру-жественное течение [17,18].…”
Section: журнал включен в перечень рецензируемых научных изданий вакunclassified
“…Так, име-ются данные, что гипер-и дислипидемия часто ассоци-ируются с ростом уровня СРБ, т.е. имеет место содру-жественное течение [17,18].…”
Section: журнал включен в перечень рецензируемых научных изданий вакunclassified
“…Для изучения влияния сахароснижающей терапии на конеч-ные точки (смертность, инфаркт миокарда, острое наруше-ние мозгового кровообращения (ОНМК)) у лиц без исходных ССЗ должны пройти десятилетия, поэтому среди данной ко-горты больных чаще изучаются факторы риска или суррогат-ные точки. В частности получены результаты исследования SPEAD-A, изучавшего влияние сахароснижающей терапии на толщину комплекса интима-медиа [37]. В данном иссле-довании применение иДПП-алоглиптина позволяло более значимо предотвращать прогрессию утолщения комплекса интима-медиа по сравнению с другими сахароснижающими препаратами у лиц без ССЗ в ана мнезе.…”
Section: первичная профилактика сердечно-сосудистых исходов у пациентunclassified
“…Recent studies have shown that aloglitpin and sitagliptin prevent the progression of carotid atherosclerosis in patients with diabetes [97,98]. Furthermore, a meta-analysis demonstrated that GLP-1-based therapy has beneficial effects on atherosclerotic markers (brain naturetic peptide, high-sensitivity C-reactive protein, plasminogen activator inhibitor-1, total cholesterol, LDL cholesterol, and triglycerides) in patients with type 2 diabetes [99].…”
Section: Diabetic Macrovascular Complicationsmentioning
confidence: 99%